Postexposure psychological sequelae in frontline health workers to COVID-19 in Andhra Pradesh, India - Keya Das; V S S. R. Ryali; R Bhavyasree; C Madhu Sekhar (Industrial Psychiatry Journal, 2021)
Introduction: Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 has engulfed the globe since December 2019. Healthcare workers remain at the forefront of this battle, and like prior pandemics face mental health challenges along with physical risks. We aimed to study the perceived stress and possible posttraumatic stress in the frontline workers exposed to active COVID-19 duties in the state of Andhra Pradesh, India. Methodology: A special voluntary, anonymous, survey-based Google questionnaire was designed with mandatory consent form and queries to clarify inclusion exclusion criteria. Tools included valid, reliable self-administered scales, namely General Health Questionnaire 12, Perceived Stress Scale and Impact of Events Scales-Revised. A purposive sampling method was adopted, by posting the survey questionnaire on WhatsApp groups of doctors, interns, and nurses working on active COVID-19 duty in Andhra Pradesh. Results: About 69.7% of the frontline workers recorded higher perceived stress and definitive posttraumatic stress disorder (PTSD) was found in 34.8%, with psychological distress recorded in 53%. Conclusion: The higher levels of perceived stress discovered in the vast majority with definitive PTSD features in a third of the sample indicates the need for provision of mental health support proactively among frontline workers on active COVID-19 duty.